Meningkatkan Kemampuan Bahasa Keaksaraan Anak Melalui Media Loose Part Pada Anak Usia 5-6 Tahun di Tk Mutiara Bongkal Malang Kecamatan Kelayang Kabupaten Indragiri Hulu - Erniati Erniati; Chindra Chindra; Elvi Wahyuni (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Abstract This study aims to improve children's literacy through the loose part method in group B children at Mutiara Bongkal Kindergarten Malang, the object of this research is early childhood creativity through activities to recognize letters and numbers using used materials or seeds to improve children's abilities in literacy. Data collection techniques used are observation to determine aspects and interviews. Data analysis techniques in this study are descriptive and quantitative. Increasing the creativity of young children through literacy activities carried out by giving tasks using loose parts to improve children's ability in literacy, namely there are 4 stages, namely: planning, implementation, observation, and reflection, which have been carried out at Mutiata Bongkal Kindergarten in Malang. Keywords: Language, Literacy, Loose Part